Epidemiological cut-off values for Vibrio parahaemo lyticus calculated from minimal inhibitory concentration data generated at 35 and 28°C - Smith, Peter; Joseph, Andrew; Baker-Austin, Craig; Kang, Nisha; Baron, Sandrine; Le Devendec, Laëtitia; Jouy, Eric; Chisnall, Thomas; Davies, Alistair R.; Schwarz, Stefan; Feßler, Andrea T.; Ahrens, Tanja; et al. (Inter-Research Science Publisher, 2024)
This work was performed to generate the data needed to set epidemiological cut-off values for minimal inhibitory concentrations (MICs) of 10 antimicrobial agents against Vibrio parahaemolyticus determined using standardised broth microdilution protocols. Eight laboratories performed broth microdilution tests with incubation at 35°C for 16 to 20 h, and 7 also performed tests on the same isolates with incubation at 28°C for 24 to 28 h. Data were analysed by the ECOFFinder and normalised resistance interpretation algorithms. The cut-off values calculated for ceftazidime, florfenicol and trimethoprim/sulfamethoxazole, 1, 1 and 0.25/4.75 µg ml-1, respectively, were the same when calculated from data obtained at both temperatures. The cut-off values calculated from data obtained at 35°C and from data obtained at 28°C were 0.25 and 0.5 µg ml-1 for enrofloxacin, 2 and 4 µg ml-1 for gentamicin, 0.5 and 1 µg ml-1 for oxolinic acid and 2 and 1 µg ml-1 for oxytetracycline, respectively. The influence of incubation temperature on MIC values was investigated by comparing MICs obtained at 35 and 28°C for a specific antimicrobial agent with a particular isolate by an individual laboratory. Results showed that 56% of 1473 of these paired MIC values were identical, while 38% differed from one another by not more than 1 dilution step. The data generated in this work will be submitted to the Clinical and Laboratory Standards Institute for consideration in their setting of internationally agreed epidemiological cut-off values for V. parahaemolyticus that are essential for interpreting antimicrobial susceptibility testing data of this species.